Creative by Way of Adaption: Ramayana Relief of Prambanan Temple - Soeprapto Soedjono (Journal of Urban Society's Arts, 2015)
Artikel ini membahas tentang proses penciptaan karya seni berdasarkan teori adaptasi sebagaimana yang didiskusikan oleh Linda Hutcheon dalam bukunya yang berjudul: A Theory of Adaptation. Penekanan pembahasan lebih diletakkan pada aspek-aspek estetis visual yang terdapat pada karya seni relief naratif yang mengelilingi sepanjang dinding bagian dalam candi Prambanan di Kalasan, Yogyakarta. Sebagaimana tema relief yang diadaptasi dari ceritera legenda Ramayana yang ditulis oleh Walmiki pada waktu silam, maka proses penciptaan relief tersebut pada masa berikutnya diyakini mengikuti prosedur teori adaptasi tersebut. This article aims to discuss the creation of arts based upon the theory of adaptation that had been laid on by Linda Hutcheon in her book called A Theory of Adaptation. The discussion has put emphasis on the elaboration of any visual aesthetics aspects embodied within the Ramayana sculptural program in the narrative relief which is encircling along Prambanan temple inner wall in Kalasan, Yogyakarta. Since the relief’s theme is derived from the ancient epic story of Ramayana legend (by Valmiki), it is plausible that the later creative process of the relief work was created through the adaptation theory procedure.